1986
DOI: 10.1007/bf02555321
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for large bowel cancer in people aged 75 years and older

Abstract: Three hundred ten predominantly male patients who were 75 years of age or older and had surgery for colorectal carcinoma had a hospital mortality rate of 9 percent and a cancer-related five-year survival of 50 percent. These results and a detailed analysis of the causes of complications and mortality were compared with the outcome of 710 patients who were treated concurrently and who were younger than 75 years. Tumors in older patients had a tendency to occur on the right side and were more locally advanced. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 17 publications
3
43
2
1
Order By: Relevance
“…While the numerical difference is large, both data is insignificant at p=0.071 and p=0.392 respectively. This finding contradicts previous literature, whereby age has inevitably been identified as a risk factor for longer LOS and in needing higher postoperative care (13)(14)(15). However, caution must be exercised in the analysis of this data as the small study sample size could be limiting the analysis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While the numerical difference is large, both data is insignificant at p=0.071 and p=0.392 respectively. This finding contradicts previous literature, whereby age has inevitably been identified as a risk factor for longer LOS and in needing higher postoperative care (13)(14)(15). However, caution must be exercised in the analysis of this data as the small study sample size could be limiting the analysis.…”
Section: Discussioncontrasting
confidence: 55%
“…Overall, there were no difference of tumour staging in the elderly cohort, a finding which seems to be equivocal in current literature (15)(16)(17)(18)22,25) Cost effectiveness of CRC surgery in the elderly patients has been a rising topic for discussion. Govaert et al recently showed that hospital cost of CRC surgery is actually lower in patients aged ≥85, with the major driver of lower cost related to ward and ICU cost (26).…”
Section: Discussionmentioning
confidence: 73%
“…The gap that has separated younger from elderly patients is closing. Although there have been recent reports from hospital series to the same effect (Bader, 1986;Kirtland and Hobler, 1986;Payne et al, 1986;Waldron et al, 1986;Irvin, 1988;Lewis and Khoury, 1988;Fielding et al, 1989;Ozoux et al, 1990;Arnaud et al, 1991), often indicating more optimistic figures (Brown et al, 1988), these reports are limited by unavoidable selection bias, especially for elderly patients. A community-based cancer registry has the advantage of providing a non-biased and detailed view of time trends in the management of cancer, without the limitations due to recruitment, which often varies with time.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of elderly colorec tal cancer patients has been reported to be somewhat poorer than that of younger pa tients, the figures ranging between a 20 to 30% reduction [9][10][11][12], It has been found that mortality and survival rates in 75-to 80-yearold patients are at least equal to those of youn ger patients. However, patients aged 80 and over more often have cancers with associated complications, a higher operative mortality, and a poorer prognosis [12][13][14],…”
Section: Introductionmentioning
confidence: 93%